1986
DOI: 10.1002/jat.2550060506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variable versus fixed exposure levels on the toxicity of acetaldehyde in rats

Abstract: The effects of exposure pattern on the toxicity of acetaldehyde vapour were investigated in 4-week inhalation studies. Male rats were exposed to 500 or 150 and 110 ppm for 6 h per day/5 days per week. One group of animals was exposed without interruption, the exposure of a second group was interrupted for 1.5 h between the first and second 3-h periods, the exposure of a third group was similarly interrupted and for six 5 min periods exposure was increased sixfold. Peak exposures of up to 3000 ppm superimposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 10 publications
1
10
1
Order By: Relevance
“…This is comparable with the NOAEC of 150 ppm found in a subacute repeated dose-study (6 h/day, 5 days/week, 4 weeks) in rats, based on histopathological findings in the OE, in particular loss of microvilli, thinning and disarrangement (Appelman et al 1986), whereas 150 ppm was a LOAEC in a subchronic study (6 h/day, 5 days/week, 13 weeks) in rats based on minimal olfactory degeneration at 150 ppm (NOAEC 50 ppm). Mild inflammation and hyperplasia of the respiratory epithelium started at 500 ppm (Dorman et al 2008).…”
Section: Part 3: Recommendation For the Derivation Of Occupational Exsupporting
confidence: 88%
“…This is comparable with the NOAEC of 150 ppm found in a subacute repeated dose-study (6 h/day, 5 days/week, 4 weeks) in rats, based on histopathological findings in the OE, in particular loss of microvilli, thinning and disarrangement (Appelman et al 1986), whereas 150 ppm was a LOAEC in a subchronic study (6 h/day, 5 days/week, 13 weeks) in rats based on minimal olfactory degeneration at 150 ppm (NOAEC 50 ppm). Mild inflammation and hyperplasia of the respiratory epithelium started at 500 ppm (Dorman et al 2008).…”
Section: Part 3: Recommendation For the Derivation Of Occupational Exsupporting
confidence: 88%
“…Acetaldehyde was the major contributor to the HI at both sites and is known to cause irritation of the olfactory epithelium at chronic exposure concentrations three times higher than those observed at Hickory and RCSP. 36,37 While the overall HI of samples collected near and remote from UNG wells was similar, the contribution of UNG emissions to the overall HI was 6 times higher near wells (12%) than remote from wells (2%) ( Table S2). At Hickory, UNG emissions accounted for approximately 44% of the total HI excluding OVOCs.…”
Section: ■ Introductionmentioning
confidence: 97%
“…An acetaldehyde exposure study on rats (0, 150, and 500 ppm, 6 h a day, 5 d a week, for 4 wk) indicated that the NOEL for acetaldehyde in rats is 150 ppm [14][15][16] . Another exposure study on hamsters (390, 1,340, and 4,560 ppm, 6 h a day, 5 d a week, for 90 d) indicated that the NOAEL for acetaldehyde in hamsters is 390 ppm 14) .…”
Section: Discussionmentioning
confidence: 99%